Peningkatan Pengetahuan Gizi Ibu Hamil untuk Mencegah Stunting melalui Kelas Ibu di Wilayah Kerja UPTD Puskesmas Sidemen - Erawati, Ni Luh Putu Sri; Ariyani, Ni Wayan; Somoyani, Ni Ketut (Sasambo: Jurnal Abdimas (Journal of Community Service), 2026)
Stunting merupakan masalah gizi kronis yang berdampak pada pertumbuhan fisik dan perkembangan kognitif anak, terutama pada 1.000 hari pertama kehidupan. Rendahnya pengetahuan gizi ibu hamil menjadi salah satu faktor risiko terjadinya stunting karena berpengaruh terhadap kualitas asupan nutrisi selama kehamilan. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan gizi ibu hamil melalui kegiatan kelas ibu di wilayah kerja UPTD Puskesmas Sidemen. Kegiatan dilaksanakan pada 4 Juli 2025 dengan melibatkan 30 ibu hamil. Metode pelaksanaan meliputi edukasi gizi, diskusi, praktik penyusunan menu, serta pre-test dan post-test pengetahuan. Hasil menunjukkan adanya peningkatan pengetahuan yang bermakna, dari rata-rata 76,67 menjadi 93 setelah edukasi. Berbagai luaran telah dicapai, di antaranya publikasi artikel media massa, unggahan video kegiatan, dan perolehan HaKI leaflet nutrisi ibu hamil. Program ini berjalan baik dengan dukungan aktif tenaga kesehatan dan mitra puskesmas, meskipun terdapat kendala keterlambatan kehadiran ibu hamil. Keberlanjutan program direncanakan melalui edukasi rutin bulanan oleh bidan dan tenaga gizi. Kegiatan ini terbukti efektif meningkatkan pengetahuan ibu hamil tentang gizi dan berpotensi berkontribusi terhadap pencegahan stunting.  Improving Pregnant Women’s Nutritional Knowledge to Prevent Stunting through Antenatal Classes in the Working Area of UPTD Puskesmas Sidemen  Stunting is a chronic nutritional problem that affects children’s physical growth and cognitive development, particularly during the first 1,000 days of Improving Pregnant Women’s Nutritional Knowledge to Prevent Stunting through Antenatal Classes in the Working Area of UPTD Puskesmas Sidemen life. Maternal nutritional knowledge plays a crucial role in determining the quality of nutrient intake during pregnancy, which directly influences fetal growth and the risk of stunting. This community service program aimed to improve pregnant women’s nutritional knowledge through a structured antenatal class at UPTD Puskesmas Sidemen. The activity was conducted on July 4, 2025, and involved 30 pregnant women. The intervention consisted of nutrition education, discussions, hands-on menu planning practice, and pre- and post-tests to measure knowledge improvement. The results demonstrated a significant increase in the average knowledge score, from 76.67 before the intervention to 93.00 afterward. Several outputs were successfully achieved, including a published mass media article, an online video documenting the activity, and intellectual property rights for a nutrition leaflet. Despite minor challenges related to participant attendance due to weather and transportation barriers, the program was implemented effectively with strong collaboration from healthcare providers and community partners. This activity proved effective in enhancing pregnant women’s nutritional knowledge and has potential to contribute to stunting prevention efforts in the region